Analysis of Incentive Factors, Performance Assessment, and Work Ethic on the Productivity of East Aceh Social Service Employees - Tanjung, Rosmaidar; Munthe, Melia Romasta; Nasution, Omar Sjarif; Pratama Syahputra, Muhammad Eka; Syafrie, Muhammad; Helmi, Tengku Ahmad (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This study aims to analyze the influence of incentives, performance assessments, and work ethic on the productivity of employees of the East Aceh Social Service. This study uses a quantitative method with a survey approach, involving 42 employees as a sample. Data were collected through questionnaires and analyzed using multiple linear regression to test the relationship between independent variables (incentives, performance appraisals, work ethic) and dependent variables (productivity). The results of the study show that the three independent variables have a significant effect on employee productivity. Work ethic had the greatest influence on productivity with a regression coefficient of 0.485, followed by performance appraisal (0.400) and incentives (0.312). The F test shows that incentives, performance appraisals, and work ethic simultaneously have a significant effect on employee productivity. The value of the determination coefficient (R²) of 0.652 indicates that 65.2% of the variation in productivity can be explained by these three variables. The results of this study emphasize the importance of fair incentives, objective performance assessments, and the development of a high work ethic in increasing employee productivity in the public sector. This study also recommends improving human resource management to support more optimal productivity.